Die invloed van rekenarisering op die leksikografiese terminologie - Harteveld, Pieter (Lexikos, 1995)
The Influence of Computerization on Lexicographical TerminologyWhere new technological developments like the computer and new scientific disciplines like computer science penetrate existing fields of study, they influence them terminologically. This is also the case with computerized lexicography. In this article recent lexicographical terminology is looked at inter alia in the light of publications by F.J. Hausmann and H.E. Wiegand in order to make provision in this terminology for the relatively new field of computer lexicography which, just like the so-called field of manual lexicography, is regarded here as a subfield of lexicography. In view of their naming, certain lexicographic phenomena are looked into more closely. New terms that refer specifically to computer lexicography, as well as alternatives to certain established terms in lexicographic theory and practice, are consequently proposed. These proposals enable the terminology of computer lexicography and the terminology of the older manual lexicography to join seamlessly. In this way, terminological unity in lexicography is ensured. Keywords: computerization, lexicography, manual lexicography, computer lexicography, lexicographical terminology, computer lexicographical terminology, terminological unity, dictionary entry, front matter entry, word list entry, back matter entry, information entry, structural marker, access entry, user access entry, computer access entry